PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR AKTIVA, DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN SUBSEKTOR PERDAGANGAN ECERAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Amelia Sinaga, Jholant Bringg Luck (EDUTECH CONSULTANT, 2019)
Determination of capital structure can be influenced by profitability, liquidity, asset structure, and sales growth. The theories used in this study are theories of profitability, liquidity, asset structure, and sales growth related to capital structure. The method used in this study is quantitative and the nature of research is explanatory. The data collection technique used is the study of documentation. Types and sources of data are secondary data in the form of financial statements of retail trading companies listed on the Indonesia Stock Exchange for the period 2012-2016. The conclusion of this study is that simultaneously profitability, liquidity, asset structure and sales growth affect the capital structure of the retail trade subsector listed on the Indonesia Stock Exchange for the period 2012-2016, partially liquidity and asset structure have a significant negative effect on capital structure, while profitability and sales growth has no significant effect on the capital structure of the retail trade subsector listed on the Indonesia Stock Exchange for the period 2012-2016.